MiR-9 Promotes Angiogenesis via Targeting on Sphingosine-1- Phosphate Receptor 1 - Yao, Xinghong; Xie, Linshen; Zeng, Ye (Frontiers in Cell and Developmental Biology, 2020)
We previously demonstrated that vascular endothelial cells released VEGF-enriched exosomes to promote the tumor vasculogenesis and progression after anti-angiogenic therapies. To clarify how microRNA (miR)-9 promoted the angiogenesis of tumor-associated endothelial cells, in the present study, we investigated the association between miR-9 and sphingosine-1-phosphate (S1P) receptors in angiogenesis. The levels of S1P1, S1P2, and S1P3 were detected in miR-9 overexpressing endothelial cells by qRT-PCR and western blot. The binding sites of miR-9 on S1P1 and S1P3 were predicted and tested by dual-luciferase reporter assays. Then, angiogenesis in endothelial cells overexpressing both S1P1 and miR-9 was detected. The results showed that miR-9 significantly inhibited S1P1 and S1P3 in both mRNA and protein levels. We predicted that binding sites exist between miR-9 and S1P1, S1P3, but only S1P1 was directly targeted by miR-9. Overexpression of S1P1 significantly suppressed the miR-9-induced angiogenesis. Therefore, miR-9 induces angiogenesis via targeting on S1P1.